Economic crises, maternal and infant mortality, low birth weight and enrollment rates: Evidence from Argentina's downturns - Guillermo Cruces; Pablo Glüzmann; Luis Felipe Calva López (Institute for the Study of Labor (IZA), 2011)
This study investigates the impact of recent crises in Argentina (including the severe downturn of 2001-2002) on health and education outcomes. The identification strategy relies on both the inter-temporal and the cross-provincial co-variation between changes in regional GDP and outcomes by province. These results indicate significant and substantial effects of aggregate fluctuations on maternal and infant mortality and low birth weight, with countercyclical though not significant patterns for enrollment rates. Finally, provincial public expenditures on health and education are correlated with the incidence of low birth weight and school enrollment for teenagers, with worsening results associated with GDP declines.
urn:nbn:de:101:1-201111213243
Keywords: I15; I25; 330; crisis; infant mortality; maternal mortality; low birth weight; poverty; Argentina; Wirtschaftskrise; Sozialprodukt; Sterblichkeit; Kindersterblichkeit; Armut; Argentinien